Frailty in Older Adults and Physical Activity - Jorge Luis Abreus Mora; Vivian Bárbara González Curbelo (Revista Finlay)
Early detection of frailty and the timely use of diagnostic, therapeutic and rehabilitative techniques can positively modify the expected expression of disability in the elderly. Early interventions, which include exercise and mobilization, help reduce the severity of associated complications and facilitate the functional recovery of this age group. Resistance, flexibility, balance and strength exercises reduce the incidence and risk of falls, morbidity and mortality and prevent functional deterioration.